INFORMATION SYSTEMS PLANNING AND CONTROL MACHINE AND SPAREPART IN PT. TRANKA KABEL - Sri Rahayu; Ir. Susi Wigiyati, MM Ir. Susi Wigiyati, MM (Jurnal Sistem Informasi, 1999)
Material information systems and spare parts are running currently at. Tranka Kabelnot support effective management decisions in the planning of spare parts, so thedecision becomes inaccurate. This is evident from the fact frequent purchases ofgoods that ultimately are not in use, but on the other hand are also common stock out.Formally planning spare parts based on the number of users within the applicableperiod and the need for a moment, without revealing the technical and economicfactors without anticipate future needs systematically. By analyzing the currentsystem can be concluded that the PT. Tranka Kabel are in need of something TrankaKabel information system which can support the planning and controlling inventory,particularly machinery parts to help smooth production and operation.